The Influence of Human Relations, Work Discipline and Work Environment on Employee Performance at PT Bank - Fakhira Khairani; Ainun Mardhiyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Employee performance can be influenced by relationships between employees, work discipline, and work environment conditions. This research aims to find out how relationships between employees, work discipline, and work environment conditions influence employee performance at PT Bank X. This research uses quantitative methods with an associative approach. The research sample consisted of 32 PT Bank X employees selected using the saturated sampling method. Data was collected through research instruments, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results show that relationships between employees, work discipline, and work environment conditions have a positive and significant influence on employee performance. Good employee relations will encourage employees to collaborate with each other and share information. High work discipline will make employees more focused and motivated to work.